RUSSIAN AND WESTERN ACADEMICS ON CHINA’S POLICY IN CENTRAL ASIA - A. Ye. Malzev (Сравнительная политика, 2015)
Central Asia plays an essential role for China’s foreign policy. Beijing has recently increased its presence in the region and now is treated as one of the main powers. This article analyzes the key studies on China’s Central Asia strategy. It focuses on the most complicated problems that experts face researching the issue. Finally an author came to the conclusion that complex approach towards China’s policy in Central Asia is not worked out yet. Most of the scholars admit that China’s share in regional politics is increasing, but they are not sure about its final goal.